Challenges And Solutions In Maintaining Indonesian Generation Z Nationalism In The Digitalization Era - Adamentha Tarigan, Timothy; Liui, Fredrick; Hanif, Muhammad; Glorino Rumambo Pandin, Moses (Jurnal Syntax Fusion, 2022)
Nowadays, Indonesia is facing a pandemic that brought us to a rapid digital transformation, which brings us to the middle of the digitalization era. One of the generations who absorb the effect of this is Generation Z. Although Generation Z mastered technology better than other generations, Generation Z’s sense of nationalism can’t fade because nationalism is necessary for a nation. The literature study method is used in this paper, where the writer collected literature materials based on some keywords in Google Scholar. Generally, challenges that Generation Z’s facing is in the form of bad characteristics of Generation Z, technology abuse, unfiltered foreign culture, and bad influence of social media & virtual world. Pancasila as the nation’s fundamental holds the main role for this problem’s solution since it contains values of life and national identity. Character education is also necessary since it holds many important aspects to stir up the sense of nationalism. Other unique approaches are also quite important, such as ethnomathematics implementation & scout extracurricular. We are lacking in solutions to fix this issue. More innovative ways need to be discovered and implemented to maintain the sense of nationalism in Generation Z.